POLITIK EKONOMI ISLAM KOMPARASI HUKUM DAN NILAI SISTEM EKONOMI DUNIA (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2016)
The Islamic Economic Doctrine is a comparative study that looks at the fundamental principles of Islamic economics, and compares them with the economic and philosophical foundations of capitalism and Marxism. It identifies through a review of theoretical economics the structural problems that lie in the current economic order. Poverty and Inequality have increased in last two decades and the millennium development goals are still far from achieved. The research identifies that lack of an ethical foundation, unbridled pursuit of self interest in production as well as in consumption, interest based financial ad monetary system are the major problematic issues in Capitalism against which mixed economy has also shown limited effectiveness. Socialism promises to create heaven on earth, but takes fundamental human rights and profit motive away and in the extreme case give way for an autocratic or totalitarian regime. Islamic economic system in its true sense is not present in any country. It is a blend of natural features present in Capitalism i.e. right to private property, private pursuit of economic interest, use of market forces etc. used along with some distinct features derived through Islamic economic teachings i.e. interest free economy, moral check on unbridled self-pursuit and provision of socio-economic justice to achieve the goals of Socialism as far as is naturally possible without denying individual freedom and profit motive